Interactions between private and public sector wages - Afonso, António (2010)
We analyse the interactions between public and private sector wages per employee in OECD countries. We motivate the analysis with a dynamic labour market equilibrium model with search and matching frictions to study the effects of public sector employment and wages on the labour market, particularly on private sector wages. Our empirical evidence shows that the growth of public sector wages and of public sector employment positively affects the growth of private sector wages. Moreover, total factor productivity, the unemployment rate, hours per worker, and inflation, are also important determinants of private sector wage growth. With respect to public sector wage growth, we find that, in addition to some market related variables, it is also influenced by fiscal conditions.